Bruton's tyrosine kinase is required for TLR2 and TLR4-induced TNF, but not IL-6, production. - Horwood, N; Page, T; McDaid, J; Palmer, C; Campbell, J; Mahon, T; Brennan, F; Webster, D; Foxwell, B (2006)
Bruton's tyrosine kinase (Btk), the gene mutated in the human immunodeficiency X-linked agammaglobulinemia, is activated by LPS and is required for LPS-induced TNF production. In this study, we have investigated the role of Btk both in signaling via another TLR (TLR2) and in the production of other proinflammatory cytokines such as IL-1beta, IL-6, and IL-8. Our data show that in X-linked agammaglobulinemia PBMCs, stimulation with TLR4 (LPS) or TLR2 (N-palmitoyl-S-[2, 3-bis(palmitoyloxy)-(2R)-propyl]-(R)-cysteine) ligands produces significantly less TNF and IL-1beta than in normal controls. In contrast, a lack of Btk has no impact on the production of IL-6, IL-8, or the anti-inflammatory cytokine, IL-10. Our previous data suggested that Btk lies within a p38-dependent pathway that stabilizes TNF mRNA. Accordingly, TaqMan quantitative PCR analysis of actinomycin D time courses presented in this work shows that overexpression of Btk is able to stabilize TNF, but not IL-6 mRNA. Furthermore, using the p38 inhibitor SB203580, we show that the TLR4-induced production of TNF, but not IL-6, requires the activity of p38 MAPK. These data provide evidence for a common requirement for Btk in TLR2- and TLR4-mediated induction of two important proinflammatory cytokines, TNF and IL-1beta, and reveal important differences in the TLR-mediated signals required for the production of IL-6, IL-8, and IL-10.